STRATEGI PEMASARAN PRODUK TABUNGAN BERHADIAH DALAM MENARIK MINAT NASABAH MENABUNG DI PT BANK SYARIAH INDONESIA KCP CEMARA ASRI - Dea Amanda Putri; Nikmah Dalimunthe (Jurnal Publikasi Manajemen Informatika, 2025)
This research aims to analyze the marketing strategy of prize-linked savings products in attracting customers to save at PT Bank Syariah Indonesia KCP Cemara Asri. The research method used is qualitative with a field study approach. Data was collected through in-depth interviews with the Consumer Banking Relationship Manager (CBRM) and observation. The results showed that BSI KCP Cemara Asri implements a marketing mix strategy that includes product, price, place, and promotion. The prize-linked savings program is the main attraction. Factors influencing customer interest include trust in the bank, profit-sharing rate, prize program, convenience, and service. This study concludes that the marketing strategy of prize-linked savings is effective in increasing the number of customers and savings funds.